2018
DOI: 10.3174/ajnr.a5545
|View full text |Cite
|
Sign up to set email alerts
|

Substantia Nigra Free Water Increases Longitudinally in Parkinson Disease

Abstract: BACKGROUND AND PURPOSE:Free water in the posterior substantia nigra obtained from a bi-tensor diffusion MR imaging model has been shown to significantly increase over 1-and 4-year periods in patients with early-stage idiopathic Parkinson disease compared with healthy controls, which suggests that posterior substantia nigra free water may be an idiopathic Parkinson disease progression biomarker. Due to the known temporal posterior-to-anterior substantia nigra degeneration in idiopathic Parkinson disease, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 40 publications
6
48
1
2
Order By: Relevance
“…This study is the first to show elevated Viso in the posterior substantia nigra in PD, and both the anterior and posterior substantia nigra in MSAp and PSP compared to healthy controls. FW ss imaging results derived from the single‐shell scan confirm previous work that FW in the posterior substantia nigra is elevated in PD, MSAp, and PSP compared to controls (Burciu et al, ; Guttuso Jr. et al, ; Ofori et al, ; Ofori et al, ; Planetta et al, ). Increased FW and Viso are likely indicative of neurodegeneration wherein the ratio of intracellular to extracellular space is reduced leading to an increase in the measured fractional volume of extracellular fluid (Pasternak et al, ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study is the first to show elevated Viso in the posterior substantia nigra in PD, and both the anterior and posterior substantia nigra in MSAp and PSP compared to healthy controls. FW ss imaging results derived from the single‐shell scan confirm previous work that FW in the posterior substantia nigra is elevated in PD, MSAp, and PSP compared to controls (Burciu et al, ; Guttuso Jr. et al, ; Ofori et al, ; Ofori et al, ; Planetta et al, ). Increased FW and Viso are likely indicative of neurodegeneration wherein the ratio of intracellular to extracellular space is reduced leading to an increase in the measured fractional volume of extracellular fluid (Pasternak et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, Viso and FW in the posterior substantia nigra are the only diffusion measures that differed in PD relative to healthy control subjects, indicating that substantia nigra differences are consistent and highly replicable across studies implementing multicompartmental models Guttuso Jr. et al, 2018;Ofori et al, 2017;Ofori et al, 2015;Planetta et al, 2016;Yang et al, 2019). Studies implementing the NODDI model in PD have shown reduced Vic in the substantia nigra (Kamagata et al, 2016), and reduced Vic along the pathway in which seeds are placed in the substantia nigra and globus pallidus (Andica et al, 2018).…”
Section: Discussionsupporting
confidence: 68%
“…As previously reported, of the 57 study participants enrolled at baseline, 18 were not available for assessment at the 3‐year time point and 1 was excluded because of a frontal lobe astrocytoma. Of the remaining 38 participants, 3 were excluded because of excessive movement during the MRI acquisition (1 PD patient and 2 HCs) and an additional HC was excluded because of corrupted MRI data that prevented QSM reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…This ventral–dorsal gradient in SN degeneration has not been previously assessed longitudinally in terms of iron accumulation in vivo in PD. However, previous studies using diffusion tensor imaging (DTI) assessments have shown the ventral posterior SN to be the most sensitive to both cross‐sectional and longitudinal changes in PD . In addition, a recent study found elevated iron levels in PD within the more ventral SN, although longitudinal changes were not assessed …”
mentioning
confidence: 95%
See 1 more Smart Citation